Pengaruh Promosi Dan Lokasi Terhadap Keputusan Pembelian Cho-Sik Pada UPT Sikka Innovation Center Maumere - Yeti, Veronika Wendelina Nona; Tonce, Yosef; Tokan, Maria Goreti Mao (Universitas Nusa Nipa Maumere, 2026)
This study aims to determine the influence of promotion and location on purchasing decisions of Cho-Sik products at UPT Sikka Innovation Center Maumere. The research employed a quantitative method with a survey approach. The sample consisted of 100 respondents selected using purposive sampling from a population of 10,149 consumers. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the assistance of SPSS version 23. The results showed that the promotion variable obtained a perception score of 84.22% (very good), the location variable scored 83.96% (good), and the purchasing decision variable scored 87.90% (very good). The regression analysis produced the equation Y = 26.851 + 0.434X₁ + 0.307X₂. Partially, promotion had a positive and significant effect on purchasing decisions, with a t-value of 4.473 and a significance level of 0.001. Likewise, location had a positive and significant effect on purchasing decisions, with a t-value of 3.343 and a significance level of 0.004. Simultaneously, promotion and location had a positive and significant effect on purchasing decisions, as indicated by an F-value of 8.264 and a significance level of 0.000. The coefficient of determination (R²) was 0.146, indicating that promotion and location explained 14.6% of the variation in purchasing decisions, while the remaining 85.4% was influenced by other factors not examined in this study. Therefore, it can be concluded that promotion and location have a positive and significant influence on purchasing decisions of Cho-Sik products at UPT Sikka Innovation Center Maumere.